Knights vs. dinosaurs - Phelan, Matt (Greenwillow Books, an imprint of HarperCollins Publishers, 2018)
With the realm at peace and few dragons about, the Knights of the Round Table are bored, so Merlin sends them to face the most terrible lizards of all--dinosaurs.